Pemodelan program holistik dalam intervensi anak stunting lost contact: studi operasional berbasis komunitas - Arfan Syahroni; Tyas Febriana; Mario Sandro; Lienda Wati (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Abstract Background: Stunting remains a major health problem in Indonesia. Although the prevalence of stunting in Indonesia has decreased from 37.2% to 21.6% in 2022, this figure still exceeds the WHO threshold of 20%. One major challenge in implementing programs is the number of children who are not reached by nutritional interventions, known as "lost contact." This group is vulnerable to being overlooked and not receiving adequate health services. Purpose: To develop a holistic, family- and village-based intervention model to address stunted children who are "lost contact". Method: This is an operational study using a mixed methods approach. A survey was conducted on 15 stunted children who were "lost contact." Quantitative and qualitative data were collected through in-depth interviews and focus group discussions (FGDs) with mothers, cadres, and village officials. Analysis was descriptive and thematic. Results: The majority of children come from families with low education (40%) and incomes below the minimum wage (UMR) (46.7%). The main factors contributing to "lost contact" are lack of tracking, low maternal awareness, geographical access constraints, and social stigma. Meanwhile, mothers' knowledge of nutrition is generally low to moderate. Conclusion: Addressing stunting with lost contact requires a holistic, community-based approach, including active tracking, contextual education, adaptive logistics distribution, and locally based behavior change campaigns.